2004
DOI: 10.1002/chir.20098
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and absolute configuration assignment of 5-amino-1,3,5-triphenyl-pentane-1,3-diol stereoisomers

Abstract: Starting from 2,4,6-triphenylpyrylium perchlorate, 5-amino-1,3,5-triphenyl-pentane-1,3-diol stereoisomers 4 were obtained in a simple two-step synthesis: reaction with hydroxylamine, and reduction with LAH of the resulting 2-isoxazoline ketone derivative 2. The eight stereoisomers of 4 were separated in a single shot on a chiral stationary phase cellulose tris(3,5-dimethylphenylcarbamate) (Chiralcel OD-H). The absolute configuration of the title compounds, intermediate 2-isoxazoline ketone 2 and isoxazoline al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It is well documented in the literature that these CSPs are also outstanding chromatographic supports to separate compounds, which are not enantiomers . As an example, the eight stereoisomers issuing from the three stereocentres in 5‐amino‐1,3,5‐triphenyl‐pentane‐1,3‐diol have been baseline separated in a single step . In the case of a pair of enantiomers, the ratio of the peak areas directly provides the enantiomeric ratio without the need for further calibration, whereas in other cases a calibration is required for quantification, as in classical HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented in the literature that these CSPs are also outstanding chromatographic supports to separate compounds, which are not enantiomers . As an example, the eight stereoisomers issuing from the three stereocentres in 5‐amino‐1,3,5‐triphenyl‐pentane‐1,3‐diol have been baseline separated in a single step . In the case of a pair of enantiomers, the ratio of the peak areas directly provides the enantiomeric ratio without the need for further calibration, whereas in other cases a calibration is required for quantification, as in classical HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…To develop the approach, our initial efforts were directed toward the synthesis of racemic amino alcohol using 6a as a model substrate. When 4.0 equiv of BH 3 ·THF was used, we observed that the conversion to the desired product 3-amino-3-phenylpropan-1-ol 2a was of 91% yield (Scheme ) . Similarly, products 2b and 2c were also isolated in good yields under the same conditions. , …”
Section: Resultsmentioning
confidence: 82%
“…In such a case, the use of chromatography on chiral support with polarimetric detection is an excellent option. [56][57][58] Having determined the chromatographic conditions and sign of first and second eluted enantiomers for each pair in rac-1, rac-2, and rac-3, it was quite easy to select the right chromatographic system to show that starting from enantiopure (1)aS,aS-1, (1)-2 and (1)-3 were obtained (Scheme 4). Chiralcel OB-H was the only column able to separate the enantiomers of the Compounds 1, 2, and 3 in the same run.…”
Section: Resultsmentioning
confidence: 99%